MODEL MEDIASI HUBUNGAN ANTARA ENTERPRISE RESOURCES PLANNING SYSTEM, SUPPLY CHAIN MANAGEMENT DAN KINERJA PERUSAHAAN - Muhammad Nawawi; Taufik Akbar (FEB Universitas Sultan Ageng Tirtayasa, 2019)
The purpose of this study is to provide empirical evidence the mediating effect of supply chain management (SCM) on the relationship between enterprise resources planning (ERP) and firm performance. The empirical analysis in this study is based on primary data obtained from a survey of 100 manufacturing companies with 78 respondents, or response rate of 39.00%. This research was conducted by the method of approach to structural equation modeling (SEM) with testing tools using partial least squares (PLS). Overall, these findings indicate that the supply chain management partially mediates the effect of ERP on firm performance. The results of this study indicate that the implementation of enterprise resources planning resulted in improved performance of the company in the long run, and supply chain management helps companies achieve performance improvement company in the future.